Parents’ and caretakers’ perceptions and concerns about accessibility of antenatal services by pregnant teenagers in Mbarara Municipality, Uganda - Rukundo, Godfrey Zari; Abaasa, Catherine; Natukunda, Peace Byamukama; Allain, Dominic (Midwifery, 2019)
Background: Uganda has one of the highest teenage pregnancy rates in Sub-Saharan Africa and the world. About a quarter of teenagers become pregnant annually. This is much higher than the global rate of 11%. When a teenager becomes pregnant, caring responsibilities are usually shared between the teenage mother and the baby’s grandmother. Previous research has largely focused on the experiences of teenagers, leaving out the parents and caregivers. This paper describes parents and caretakers’ percep- tions and concerns about accessibility of antenatal services by pregnant teenagers in three divisions of Mbarara Municipality in southwestern Uganda. Methods: This was a qualitative cross-sectional descriptive study. Thirty in-depth interviews with parents and caregivers were conducted. The study was conducted in the Nyamitanga, Kakoba and Kamukuzi di- visions in Mbarara Municipality, southwestern Uganda. Data analysis was done manually by identifying emergent themes which were then coded and organized into concepts which were later developed into explanations. Results: According to parents and other caregivers, teenage pregnancy is considered a significant chal- lenge both for themselves and for the teenagers. Often, pregnant teenagers lack information on the avail- able antenatal care services. They struggle with stigma and also lack social and financial support from parents. In addition, the teenagers lack support from reproductive health workers. The parents and care- givers also struggle with the stigma of their children’s pregnancy and are often unaware of any available teenager friendly ANC services. Conclusions: Parents and caregivers find it difficult to cope with their children’s pregnancy. They are not aware of any existing teenager-friendly antenatal services, yet antenatal services specifically targeting teenagers are necessary. In planning programs for antenatal services, parents and caregivers also need to be equipped with knowledge and skills required for them to guide and support the pregnant teenagers.
Keywords: Teenage pregnancy; Caregiver; Perceptions; Concerns; Uganda